Long‐term clinical experience with cardiac contractility modulation therapy delivered by the Optimizer Smart system. (17th May 2021) - Kuschyk, Jürgen; Falk, Peter; Demming, Thomas; Marx, Oliver; Morley, Deborah; Rao, Ishu; Burkhoff, Daniel
Abstract: Aims: We assessed long‐term effects of cardiac contractility modulation delivered by the Optimizer Smart system on quality of life, left ventricular ejection fraction (LVEF), mortality and heart failure and cardiovascular hospitalizations. Methods and results: CCM‐REG is a prospective registry study including 503 patients from 51 European centres. Effects were evaluated in three terciles of LVEF (≤25%, 26–34% and ≥35%) and in patients with atrial fibrillation (AF) and normal sinus rhythm (NSR). Hospitalization rates were compared using a chi‐square test. Changes in functional parameters of New York Heart Association (NYHA) class, Minnesota Living with Heart Failure Questionnaire (MLWHFQ) and LVEF were assessed with Wilcoxon signed‐rank test, and event‐free survival by Kaplan–Meier analysis. For the entire cohort and each subgroup, NYHA class and MLWHFQ improved at 6, 12, 18 and 24 months ( P  < 0.0001). At 24 months, NYHA class, MLWHFQ and LVEF showed an average improvement of 0.6 ± 0.7, 10 ± 21 and 5.6 ± 8.4%, respectively (all P  < 0.001). LVEF improved in the entire cohort and in the LVEF ≤25% subgroup with AF and NSR. In the overall cohort, heart failure hospitalizations decreased from 0.74 [95% confidence interval (CI) 0.66–0.82] prior to enrolment to 0.25 (95% CI 0.21–0.28) events per patient‐year during 2‐year follow‐up ( P  < 0.0001). Cardiovascular hospitalizations decreased from 1.04 (95% CI 0.95–1.13) events per patient‐year prior to enrolment to 0.39 (95% CI 0.35–0.44) events per patient‐year during 2‐year follow‐up ( P  < 0.0001). Similar reductions of hospitalization rates were observed in the LVEF, AF and NSR subgroups. Estimated survival was significantly better than predicted by MAGGIC at 1 and 3 years in the entire cohort and in the LVEF 26–34% and ≥35% subgroups. Conclusions: Cardiac contractility modulation therapy improved functional status, quality of life, LVEF and, compared to patients' prior history, reduced heart failure hospitalization rates. Survival at 1 and 3 years was significantly better than predicted by the MAGGIC risk score. Abstract : The CCM‐REG registry study of cardiac contractility modulation. CCM, cardiac contractility modulation; LVEF, left ventricular ejection fraction; MAGGIC, Meta‐Analysis Global Group in Chronic Heart Failure; MLWHFQ, Minnesota Living with Heart Failure Questionnaire; NYHA, New York Heart Association.